DOES REPURCHASE INTENTION OCCUR CAUSED BY SERVQUAL, PRICE, PLACE, PROMOTION AND CUSTOMER SATISFACTION AS MEDIATION IN PT. X MULTIFINANCE COMPANY? - Sofiawati, Rifa; Salim, Lina (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study aims to determine the influence of SERVQUAL, price, place, and promotion on repurchase intention with customer satisfaction mediation. The object of this research is a debtor registered in the system of one multi finance company in Jakarta. Data collection was carried out using probability sampling with simple random sampling technique with a total of 213 respondents. Empirical data processing uses the Structural Equation Model (SEM) method of the 8 hypotheses proposed, only 4 hypotheses are accepted. The results of the analysis proved that SERVQUAL has no direct effect on repurchase intention, but has an indirect effect on repurchase intention with customer satisfaction as mediation. The price has a direct and indirect effect on repurchase intention. Promotion is found to have a direct influence on repurchase intention but no indirect influence on repurchase intention. Only place has no direct or indirect effect on repurchase intention.